RANCANG BANGUN SISTEM MANAJEMEN KOST BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Ahmad Nurfaqih; Eko Budihartono; Syefudin Syefudin (INTECOMS: Journal of Information Technology and Computer Science, 2026)
This study addresses the limitations of conventional operational management at Elang Indah Boarding House in Tegal, which is susceptible to data loss, administrative inefficiencies, delays in monthly rental payments, and unstructured facility complaint records. The study aims to develop a web-based boarding house management information system to automate administrative processes, implement an automated billing notification feature through a WhatsApp Gateway, and provide a digital ticket-based platform for handling tenant complaints. The research employed the Waterfall software development model, consisting of the planning, requirements analysis, system design, implementation, testing, and deployment phases. System architecture was designed using Unified Modeling Language (UML) and Entity Relationship Diagrams (ERD), while the application was developed using the Laravel 12 framework and MySQL database. Functional testing was conducted using the Black-Box Testing approach to verify the performance of all system features. The findings demonstrate that the developed system functions effectively, with all features operating as expected without significant errors during testing. The integrated system enables real-time room availability management, simplifies financial payment verification, automates monthly billing notifications via WhatsApp, and provides a transparent and well-organized mechanism for recording and resolving tenant complaints. The implementation of this system enhances administrative efficiency, improves data accuracy, and supports more effective operational management of boarding house services. Therefore, the proposed web-based management system represents a practical and reliable solution for modernizing boarding house operations and improving service quality for both property managers and tenants.